(untitled) (Tempo e Argumento, 2020)
Political and social struggles are visual. Apart from the ceremonial acts that sometimes involves politics, every agency that is developed in the political arena is also a visual phenomenon. Cartoons, as inherent and prominent parts of the written press, are also visual communicative actions, and are perceived as specific political actions, with importance and effect on the public, political and social space of appearance (Arendt). They become documents of their time and of a particular social-political group and show themselves in the form of representation, acting in this space of the political. Considering these characteristics of cartoons, the work of German cartoonist Marie Marcks, considered one of the main voices of German feminism, is revisited on this paper. Active since the 1960s, her drawings are widely accepted, having entry in the mainstream media. They directly address themes dear to feminism, even in a time that is still resistant to them. Divided into three parts, the paper explores the conceptualization of the public / political space and its visuality, characterizing the space through which cartoons move as well as their specificity in the political space. It is followed by a brief biography of Marie Marcks and a description of the conjuncture of her performance so that, based on the documentary method, some of her most representative works are analysed, giving thus an account of the historiographical and technical background of Marcks’ agency. Keywords: Marie Marcks. Cartoons. Public opinion. Politics. Feminism.